Application of phage display technology for the production of antibodies against Streptococcus suis serotype 2 - Pattarawadee Sulong; Natsinee Anudit; Suphachai Nuanualsuwan; Segura Mariela; Kannika Khantasup (PLoS ONE, 2021)
Streptococcus suis (S. suis) serotype 2 infection is a problem in the swine industry and responsible for most cases of human infection worldwide. Since current multiplex PCR cannot differentiate between serotypes 2 and 1/2, then serotype-specific antibodies (Abs) are required for serotype identification to confirm infection by serotype 2. This study aimed to generate Abs specific to S. suis serotype 2 by phage display from a human heavy chain variable domain (VH) antibody library. For biopanning, whole cells of S. suis serotype 2 were used as the target antigen. With increasing selection stringency, we could select the VH Abs that specifically bound to a S. suis serotype 2 surface antigen, which was identified as the capsular polysaccharide (CPS). From ELISA analysis, the specific phage clone 47B3 VH with the highest binding activity to S. suis serotype 2 was selected and shown to have no cross-reactivity with S. suis serotypes 1/2, 1, and 14 that shared a common epitope with serotype 2 and occasionally cause infections in human. Moreover, no cross-reactivity with other bacteria that can be found in septic blood specimens was also observed. Then, 47B3 VH was successfully expressed as soluble 47B3 VH in E. coli TG1. The soluble 47B3 VH crude extract was further tested for its binding ability in a dose-dependent ELISA assay. The results indicated that the activity of phage clone 47B3 was still retained even when the Ab occurred in the soluble form. A quellung reaction demonstrated that the soluble 47B3 VH Ab could show bioactivity by differentiation between S. suis serotypes 2 and 1/2. Thus, it will be beneficial to use this VH Ab in the diagnosis of disease or discrimination of S. suis serotypes Furthermore, the results described here could motivate the use of phage display VH platform to produce serotyping antibodies.